Associating and Tuning Sodium and Oxygen Mixed‐Ion Conduction in Niobium‐Based Perovskites. (23rd January 2020) - Gouget, Guillaume; Mauvy, Fabrice; Chung, U‐Chan; Fourcade, Sébastien; Duttine, Mathieu; Braida, Marc‐David; Mercier, Thierry Le; Demourgues, Alain
Abstract: Pure ionic conductors as solid‐state electrolytes are of high interest in electrochemical energy storage and conversion devices. They systematically involve only one ion as the charge carrier. The association of two mobile ionic species, one positively and the other negatively charged, in a specific network should strongly influence the total ion conduction. Nb 5+ ‐ (4d 0 ) and Ti 4+ ‐based (3d 0 ) derived‐perovskite frameworks containing Na + and O 2− as mobile species are investigated as mixed ion conductors by electrochemical impedance spectroscopy. The design of Na + blocking layers via sandwiched pellet sintered by spark plasma sintering at high temperatures leads to quantified transport number of both ionic charge carriers t Na+ and t O2− . In the 350–700 °C temperature range, ionic conductivity can be tuned from major Na + contribution ( t Na+ = 88%) for NaNbO3 to pure O 2− transport in NaNb0.9 Ti0.1 O2.95 phase. Such a Ti‐substitution is accompanied with a ≈100‐fold increase in the oxygen conductivity, approaching the best values for pure oxygen conductors in this temperature range. Besides the demonstration of tunable mixed ion conduction with quantifiable cationic and anionic contributions in a single solid‐state structure, a strategy is established from structural analysis to develop other architectures with improved mixed ionic conductivity. Abstract : The transport numbers of sodium cations and oxygen anions are quantified in niobate pervoskites via an original method using sandwiched pellets with solid Na + ‐blocking/O‐conducting layers. Above 350 °C, charge carriers switch from major Na + /minor O 2− for NaNbO3 to exclusive O 2− for NaNb0.9 Ti0.1 O2.95 . This first evidence of mixed‐ion Na + /O 2− underlies a novel strategy toward improved ionic conductivity in perovskite‐derived structures.